Partial Support for the Eleventh Conference on Hunting and Gathering Societies, 2015 - Andrey Petrov (Arctic Data Center, 2017)
The study of hunter-gatherer societies around the world, and in the Arctic and Alaska in particular, became a major field within the social and human sciences five decades ago. The goal of the Eleventh Conference on Hunting and Gathering Societies (CHAGS XI) is to continue the development of a unified field of hunter-gatherer studies. The general question of CHAGS XI therefore is how the results of the last 50 years and new research agendas can be utilized for the present and future. While many hunter-gatherers are forced to give up their ways of life and subsistence practices, they figure prominently in public discourses on ecological and ideological alternatives to industrial society. CHAGS XI will attract a variety of stakeholders in these debates, including indigenous representatives, NGOs, scholars, etc., from the U.S. and other countries. Based on fieldwork and research from the full spectrum of hunter-gatherer ways of life and from all perspectives scientific disciplines have to offer, the purpose of CHAGS XI is to bring hunter-gatherer studies back to the center of the human and social sciences. The conference will encourage discussions that will provide the social sciences and other research areas with in-depth understanding of hunter-gatherer societies in the United States, Arctic and globally. Through publication of the keynote addresses, results will be widely disseminated to local, national and international groups concerned with hunter-gatherer societies.